Intellectual development before and after the onset of infantile spasms: A controlled prospective longitudinal study in tuberous sclerosis. Issue 1 (13th January 2014) - Humphrey, Ayla; MacLean, Cathy; Ploubidis, George B.; Granader, Yael; Clifford, Michelle; Haslop, Maisy; Neville, Brian G.R.; Yates, John R.W.; Bolton, Patrick F.; ,
Summary Objective Infantile spasms (IS) have long been suspected to be a risk factor for impairment in intellectual development, but there are no controlled, prospective longitudinal data in well‐characterized conditions to confirm this suspicion. We tested the hypothesis in a longitudinal study of children with tuberous sclerosis (TS), who have a high risk of developing IS. Methods Eleven infants with TS were recruited and studied longitudinally using the Mullen Scales of Early Learning. Seizure histories were assessed using a structured parent interview and by review of medical notes. Intellectual development was examined in relation to the onset and length of exposure to IS and other types of seizures. Results Six children developed IS and five children developed other types of seizure disorders. Among those that developed IS, estimated mean IQ dropped significantly (nonparametric test for trend p = 0.002) from 92 (prior to onset of spasms) to 73 (after exposure to IS for a month or less) and 62 (after exposure to IS for more than a month). By contrast, there was no significant drop in estimated IQ among the five infants exposed to other types of seizure disorders (nonparametric test for trend p = 0.9). All six children exposed to infantile spasms developed clinically significant intellectual impairment. Significance These data provide the first clear evidence of clinically significant, dose dependent, impairment in intellectual development following exposure to infantile spasms. The mechanisms underlying this developmental impairment and methods for preventing it require in depth study.